Animals in disasters - Green, Dick (Butterworth-Heinemann, an imprint of Elsevier, 2019)
Animals in Disasters is a comprehensive book on animal rescue written by Dr. Dick Green who shares his experiences, best practices and lessons learned from well over 125 domestic and international disasters. It provides a step-by-step process for communities and states to more effectively address animal issues and enhance their animal response capabilities. Sections include an overview of the history of animal rescue, where we are today, and the steps needed to better prepare for tomorrow. This how-to book for emergency managers who want to develop programs, craft policy, and build response capability/capacity is an ideal companion to their work.